INCREASING READING LITERACY OF GRADE V ELEMENTARY SCHOOL STUDENTS USING FLIPBOOK-BASED LEARNING MEDIA - Yantik, Fani; Yuwana, Setya; Hendratno (VISI : Jurnal Ilmiah Pendidik dan Tenaga Kependidikan Pendidikan Non Formal, 2023)
This study aims to describe the process of developing instructional media, the quality of the media which includes the validity, practicality and effectiveness of using flipbook-based learning media to increase story reading literacy in fifth grade students of MI Sabilillah Sampang. This development research uses the Four-D model. The subjects consisted of 28 students of class V. The data collection techniques used were observation, questionnaires and tests. The results showed that media validation obtained an average value of 4.53 with a proportion of 91%, teacher activity received an average value of 64 with a proportion of 91% and student activity obtained an average value of 65 with a proportion of 95%. Flipbook-based learning media to increase literacy in reading stories on the effectiveness aspect using the N-gain test 4 students in the medium category and 24 students in the high category. Based on price data t-statistics = 15.05 > t-table = 2.052, there is a difference significant between X1 and X2 . There is a significant difference in the results of the pretest and posttest. So it can be concluded that learning media based on Filpbook is effective to use.